The effect of rust layer damage on the corrosion resistance of Q420 bridge steels - Zexian Wang; Weichen Xu; Binbin Zhang; Junyi Gao; Canming Li; Guobao Li; Rongling Zhang; Baorong Hou (Journal of Materials Research and Technology)
The rust layer is very important for bridge weathering steels. The compactness, composition and structure of rust layers are the main factors for the corrosion resistance. The rust layer may be damaged to various extents in practical service environment. The effect of damage on the rust layer is significant for assessing and predicting the corrosion resistance and durability of bridge weathering steels. A new experimental method has been introduced in this work to achieve different levels of artificial damage on the rust layer. A blade was used to control the damaged area and depth of the rust layer. It was found that both the bare and rusted surface of Q420qDNH bridge steel exhibited better corrosion resistance than Q420qDZ25 bridge steel, mainly due to the larger amount of alloying elements and α-FeOOH in Q420qDNH. The corrosion resistance of both steels exhibited a declining trend as the level of rust layer damage progressed from PM (partially mildly damaged) to PS (partially severely damaged), OM (overall mildly damaged), and OS (overall severely damaged). The rust layer resistance of Q420qDNH bridge steel was more sensitive to rust layer damage as a result of uneven distribution of alloying elements and oxidizing agents between outer and inner rust layer. When the damage reached a certain level, the corrosion resistance of both steels decreased sharply.